Creating A Future (Symphony in the Flint Hills, 2016)
Abraham Lincoln said, “The best way to predict your future is to create it.” Flint Hills residents are applying imagination and original ideas to create a bright future for the region.
Keywords: Abraham Lincoln; economic opportunities; inspiration; Flint Hills; enlightenment; creative economy; golden future; Place; Amanda Maciuba